LEFT ATRIAL MECHANICS ASSESSED BY SPECKLE-TRACKING ECHOCARDIOGRAPHY IN ADULT PATIENTS UNDERGOING HEMODIALYSIS: A SYSTEMATIC REVIEW - Mainka, Tomasz; Sergejuk, Emil; Kotlarski, Wojciech; Kotlarska, Klaudia Magdalena (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Cardiovascular disease remains the leading cause of morbidity and mortality in patients with end-stage renal disease undergoing maintenance hemodialysis. In this population, conventional echocardiographic parameters may not fully detect early atrial dysfunction or adequately reflect the complex hemodynamic effects of recurrent volume shifts. Speckle tracking echocardiography has emerged as a promising tool for the assessment of left atrial mechanics, including reservoir, conduit, and contractile function.Methods: This systematic review was conducted in accordance with the PRISMA framework. A PubMed/MEDLINE search was performed using predefined terms related to left atrial strain, left atrial mechanics, speckle-tracking echocardiography, hemodialysis, and end-stage renal disease. Studies were eligible if they included adult patients undergoing maintenance hemodialysis and assessed left atrial deformation using speckle-tracking echocardiography. Seven studies met the inclusion criteria and were included in the qualitative synthesis.Results: Across the included studies, left atrial strain was consistently impaired in adult hemodialysis patients and was associated with markers of diastolic dysfunction, elevated filling pressures, atrial remodeling, and dialysis-related loading changes. Left atrial reservoir strain emerged as the most clinically informative parameter and demonstrated independent prognostic value for major adverse cardiovascular events and mortality in prospective studies. In addition, impaired left atrial deformation and strain rate were associated with an increased risk of paroxysmal atrial fibrillation.Conclusions: Left atrial mechanics assessed by speckle-tracking echocardiography appear to provide clinically relevant information in adult patients undergoing hemodialysis. Left atrial strain may serve as a sensitive imaging biomarker of subclinical cardiovascular dysfunction and may improve cardiovascular risk stratification in this population. However, further prospective multicenter studies are required to standardize methodology and confirm the role of left atrial strain in routine clinical practice.